Maximum Power Point Tracking Interleaved Boost Converter Using Cuckoo Search Algorithm on The Nano Grid System - Taufik Hidayat; Mohammad Zaenal Efendi; Farid Dwi Murdianto (Department of Electrical Engineering ITS and FORTEI, 2021)
The problems of using solar panels include the power and efficiency that can be achieved by solar panels during conditions where the surface of the solar panel is covered by shadows, because the performance of the solar panels is affected by the amount of sunlight received and the temperature of the solar panels. Then, a solution appears to overcome the problem, called Maximum Power Point Tracking or a technique to get the maximum output power from solar panels. Initially, MPPT worked with conventional methods, one of which was Perturb and Observe. Furthermore, the MPPT method on solar panels continues to develop to solve problems during partial shade conditions. The development of this conventional method is called the metaheuristic method, an example of which is the Cuckoo Search Algorithm method implemented in this research. This method is characterized by the Levy Flight equation in generating duty cycle values so that it can reach the maximum peak power of solar panels. The system built in this research is also supported by the highly efficient Interleaved Boost converter. Based on simulation results show that the power that can be generated by the MPPT Cuckoo Search Algorithm is higher than the MPPT Perturb and Observe, which is 121.23 W compared to 72.38 W.Keywords: automatic, humidity sensor YL-69, microcontroller, mint leaves, nourishing system, watering system, RTC.